Production of viable seeds from the seedling lethal mutant ppi2-2 lacking the atToc159 chloroplast protein import receptor using plastic containers, and characterization of the homozygous mutant progeny - Tada, Akari; Adachi, Fumi; Kakizaki, Tomohiro; Inaba, Takehito (Frontiers in Plant Science, 2014)
Biogenesis of chloroplasts is essential for plant growth and development. A number of homozygous mutants lacking a chloroplast protein exhibit an albino phenotype. In general, it is challenging to grow albino Arabidopsis plants on soil until they set seeds. Homozygous albino mutants are usually obtained as progenies of heterozygous parents. Here, we describe a method of recovering seeds from the seedling lethal Arabidopsis mutant ppi2-2, which lacks the atToc159 protein import receptor at the outer envelope membrane of chloroplast. Using plastic containers, we were able to grow homozygous ppi2-2 plants until these set seed. Although the germination rate of the harvested seeds was relatively low, it was still sufficient to allow us to further analyze the ppi2-2 progeny. Using ppi2-2 homozygous seeds, we were able to analyze the role of plastid protein import in the light-regulated induction of nuclear genes. We propose that this method be applied to other seedling lethal Arabidopsis mutants to obtain homozygous seeds, helping us further investigate the roles of plastid proteins in plant growth and development.